Generation of ultrafast terahertz radiation pulses on metallic nanostructured surfaces - Welsh, Gregor H.; Wynne, Klaas (Optics express, 2009)
A resonant "incoherent" rectification process is presented relying on the excitation of surface plasmons on a nanostructured metal surface. Excitation of gold and silver films with 800-nm femtosecond laser pulses results in the emission of terahertz radiation with an angle-dependent efficiency and an approximately third-order power dependence. It is shown that the source of this terahertz pulse generation is the surface-plasmon-assisted multiphoton ionization and ponderomotive acceleration in the evanescent field of the surface plasmon. Simple models are used to understand the forces and dynamics near the surface.